2019
DOI: 10.1007/s11250-019-02117-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam explosion of oil palm frond and empty fruit bunch on nutrient composition and ruminal fermentation characteristics

Abstract: In this study, we evaluated the effect of steam explosion of oil palm frond (OPF) and oil palm empty fruit bunch (EFB) on nutrient composition and ruminal fermentation characteristics in vitro. The results showed that steam explosion decreased NDF (P < 0.01), ADF (P < 0.01), and hemicellulose content (P < 0.01) in OPF and EFB. Steam explosion improved the effective energy value of OPF and EFB. In vitro fermentation results revealed that 72-h gas production capacity of OPF and EFB increased by 12.60and 85.06% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Steam explosion is one of the physical process that has been studied extensively for upgrading the LCB for ruminant feeds (Mokomele et al 2018;Rusli et al 2019;Wu et al (2020). This method typically proceed by rapidly heating the LCB at relatively high temperatures (160-260°C) and by high-pressure steam (0.7-4.8 MPa) and terminated by explosive decompression (Kumar & Sharma 2017).…”
Section: Mechanical and Physical-based Processes Of Lcbmentioning
confidence: 99%
See 1 more Smart Citation
“…Steam explosion is one of the physical process that has been studied extensively for upgrading the LCB for ruminant feeds (Mokomele et al 2018;Rusli et al 2019;Wu et al (2020). This method typically proceed by rapidly heating the LCB at relatively high temperatures (160-260°C) and by high-pressure steam (0.7-4.8 MPa) and terminated by explosive decompression (Kumar & Sharma 2017).…”
Section: Mechanical and Physical-based Processes Of Lcbmentioning
confidence: 99%
“…Other study in dairy cow (Wang et al 2020) showed that the NDF and ADF digestibility of corn stover pretreated by steam explosion increased by 26.1 and 27.1%, respectively and methane production decreased by 9.5%. Using steam explosion process on oil palm empty bunch increase metabolizable energy by 13.5% when fed to steer (Wu et al 2020). In the same study, increased total ruminal VFA concentration by 17.3% was also detected when oil palm fronds were pretreated by steam explosion.…”
Section: Response Of Ruminants To Mechanically and Physically Process...mentioning
confidence: 99%
“…Hence, efforts are being made to develop effective treatment methods for OPF to enhance its nutritional quality as feedstuff needed for the development of new feeding strategies and forages, and prevent the scarcity of balanced feeds [8]. The improvement of the nutritional value of OPF is one of the latest developments in oil palm waste management for exploiting the potential of locally available feedstuffs and for optimising its utilisation as an animal feed resource [9].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…A c c e p t e dA r t i c l e and the accessibility of enzymes, thereby increasing the biodegradability of plant cell walls and fibre fermentation. Wu et al[9] showed that steam explosion can improve the effective OPF metabolisable energy (ME) value and decrease the hemicellulose content of OPF from 22.81 to 18.80%. For instance, steam explosion treatment is an important method for aiding the release of OPF cellulose implanted between hemicelluloses and lignin and is more applicable to rumen fermentation, hydrolysis and densification processes.…”
mentioning
confidence: 99%
“…Hence, efforts are being made to develop effective treatment methods for OPF to enhance its nutritional quality as feedstuff needed for new fodders feeding strategies and prevent the scarcity of balanced feeds (Rusli et al, 2019). The improvement of the nutritional value of OPF is one of the latest developments in oil palm waste management for exploiting the potential of locally available feedstuffs and optimising its utilisation as an animal feed resource (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%